Can work from home help balance the parental division of labor? - Hans-Martin von Gaudecker; Radost Holler; Lenard Simon; Christian Zimpelmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This study examines how the Covid-19 pandemic-induced shift towards remote work has influenced parents' allocation of non-market and market work. Utilizing a probabilitybased panel survey and comprehensive administrative records from the Netherlands covering the years 2014 to 2021, we demonstrate that the potential for remote work has been significantly realized only after the onset of the pandemic. Simultaneously, following a brief period of school and daycare closures, the total time parents spent on childcare returned to pre-pandemic levels. Notably, while the potential for remote work was associated with reduced childcare provision before the pandemic, this relationship reversed post-pandemic onset. We interpret this shift as an indication of increased flexibility for parents, with fathers experiencing greater gains than mothers. Consequently, the division of childcare duties has become more equitable, and mothers have increased their working hours. Our findings suggest that broader acceptance of remote work by employers could foster greater gender convergence in the intra-household division of labor.
Keywords: J13; J16; J22; 330; job flexibility; remote work; childcare; division of labor; time-use data